2018
DOI: 10.1103/physrevb.98.104510
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gap anisotropy on the spin resonance peak in the superconducting state of iron-based materials

Abstract: Spin resonance in the superconducting state of Fe-based materials within the multiorbital model with unequal anisotropic gaps on different Fermi surface sheets is studied. On the basis of the model gap function and the one calculated within the spin fluctuation theory of pairing, I show that the resonance peak shifts to higher frequencies with increasing the zero-amplitude gap magnitude. On the contrary, with increasing the gap anisotropy, it shifts to lower frequencies and lose some intensity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 90 publications
3
10
0
Order By: Relevance
“…In the superconducting state, a clear spin-resonance is observed around the stripe-type wave vectors [144] (see Figure 7a,d, later confirmed in an experiment on detwinned FeSe; Figure 7g), showing a consistent behavior in energy and momentum with a spin-fluctuation-mediated superconducting pairing mechanism [162,219,220]. Polarized neutron measurements found that low-energy magnetic fluctuations, including the superconducting resonance, are mainly along the c-axis [158].…”
Section: Spin Fluctuations In Superconducting Statesupporting
confidence: 57%
“…In the superconducting state, a clear spin-resonance is observed around the stripe-type wave vectors [144] (see Figure 7a,d, later confirmed in an experiment on detwinned FeSe; Figure 7g), showing a consistent behavior in energy and momentum with a spin-fluctuation-mediated superconducting pairing mechanism [162,219,220]. Polarized neutron measurements found that low-energy magnetic fluctuations, including the superconducting resonance, are mainly along the c-axis [158].…”
Section: Spin Fluctuations In Superconducting Statesupporting
confidence: 57%
“…It is important to note that the choice of coupling mechanism limits the typology of order parameter obtainable; in the specific case of IBS and of AFM spin fluctuations the only order parameter symmetry allowed is s ± [11,35]. This specific state was chosen for the theoretical analysis because most experimental data point towards it [36][37][38] and we find it is compatible with our data as well.…”
Section: E Eliashberg Modelingsupporting
confidence: 71%
“…Notice that the hyperfine field adds to zero along the orange lines and is finite along the green lines. NaFe 1−x Co x As, although the spin density wave itself has a zero-average magnetic moment along all crystalline directions and both phenomena occur in different parts of the Fermi surface [63][64][65]. The behavior we find here has not been observed in the iron-pnictide superconducting family, as it directly connects the anisotropic structure of the local magnetic order with the anisotropic superconducting gap.…”
Section: (C) Right Panel]mentioning
confidence: 54%